KONTROVERSI KEPEMIMPINAN POLITIK PEREMPUAN PERIODE PERTENGAHAN: Kasus Pemerintahan Syajarat al-Durr Masa Dinasti MamlÃ»k - Rofiq, Ahmad Choirul (Kodifikasia, 2012)
Historical review shows us that Syajarat al-Durr was a phenomenal figurein the Mamluk dynasty. She was a slave who become a leader. Howeverher political leadership arose a clash and strife among the Muslims. Thosewho agreed to accept her government thought that Syajarat al-Durr wasthe proper one who could prove her ability to manage the government,but those who refused her believed that the community that is governedby a woman will be unsuccessful forever because the messenger (pbuh)has said that in his saying. There were two political policies performed bySyajarat al-Durr, i.e. expelling the crusaders from Egypt and strengtheningthe public support to the government of Syajarat al-Durr.